Kompetensi Kepribadian Guru Pendidikan Kristen Menurut Matius 23 dan Implikasinya di Sekolah Menengah Pertama Negeri 1 Moro’o - Roh Armawati Gulo (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
A Christian Educator does not display an attitude of humility and sincerity in carrying out his profession. He is limited to the respect and material he obtains. The research in this manuscript has a direction to conduct a study on the personality competence of PK teachers from the narrative story of the teacher (Rabbi) based on Matthew 23 and analyze its implications at SMP Negeri 1 Moro’o, West Nias. Matthew 23 as a harsh criticism of the practice of teacher function personality that is not integral as a teacher. The research method applies qualitative principles with a content analysis approach. The results of the study indicate that personality competence based on Matthew 23 is the attitude of PK teachers who display a sense of brotherhood, integrity, become facilitators, and remain humble. The implications of teacher personality competence at SMP Negeri 1 Moro’o result in an increase in the quality of learning, the formation of student spirituality, and the creation of a conducive learning process. Thus, Matthew 23 has implications for the development of teacher personality competence in the current and future contexts so as not to repeat the same mistakes as previous religious teachers.